Implementasi Artificial intelligence dalam Pembelajaran di Sekolah Dasar: Quizizz dan Diffit AI - Tuningsih, Suci; Wahyuningsih, Putri Indah (LPPM UNIVERSITAS DIAN NUSWANTORO, 2025)
The development of information technology in the field of education is not always in line with the use of technology by educators in the learning process. The main objective of this community service is to improve elementary school teachers' understanding of the use of artificial intelligence in the learning process. The types of artificial intelligence used are Diffit AI and Quizziz. This community service was carried out at MI Ma'arif Nurul Haromain located in Tuksono Village, Kulon Progo. The participants in this activity were 17 teachers. The results of the activity show that the use of Difft AI and Quizizz in learning in elementary schools has great potential to improve the quality of education. Teachers can be more productive and efficient in creating questions and worksheets, while students are more enthusiastic and motivated to learn. In addition, the use of these tools shortens the time for teachers to prepare learning administration, so that teachers have more time to interact with students in class. Continuous collaboration and training are needed so that this technology can be optimized to support more innovative and inclusive education.